Optimal policy and the risk properties of human capital reconsidered - Dan Anderberg (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper considers how optimal education and tax policy depends on the risk properties of human capital. It is demonstrated that a key feature of human capital investments is whether they increase or decrease wage risk. In a benchmark model it is shown that this feature alone determines whether a constrained optimal allocation should be characterized by a positive or a negative education premium. In the same model a positive intertemporal wedge is optimal. A set of generalizations, including non-observability of education, non-observability of consumption, and temporal resolution of uncertainty, are then considered to examine the robustness of these results.
Keywords: D81; H21; I21; 330; Education; optimal taxation; risk; Bildungsinvestition; Entscheidung bei Risiko; Optimale Besteuerung; Bildungspolitik; Theorie